Diseño y simulación de una cortadora de materiales del tipo waterjet para uso industrial (2020)
Abrasive WaterJet Cutting (AWJ) is a modern technology that has the ability to cut any type of material without producing thermally affected areas (ZATs) as no heat input is generated during it. This project shows and studies, through computational fluid dynamics (CFD), the behavior of water and abrasive particles used for this type of cuts in machine design, in order to demonstrate the feasibility of the proposed design. This analysis uses the k- s turbulenceεmodel, since before other models, it is better coupled to the fenorless to evaluate and generates a lower consumption of computational resources; as well, the configuration of a mixture fluid and the creation of a solid drag and impact particle is performed. For the design of the waterjet, multiple commercial parts and articles related to the theme were examined, in order to select the appropriate measurements and materials, relying on standardized parts that are easily obtained with suppliers and companies mostly domestic manufacturers, in order to create a machine that responds to the needs of the country's small and medium-sized industries. This study demonstrates the feasibility of the design of the sustained cutting machine with different types of hydraulic calculations specific to this type of hydraulic machines, reaching optimal fluid speeds that manage to accelerate the particle sufficiently according to previous research and optimal working behavior during simulations performed under a test of different variables using the characteristics of the material closest to the abrasive used in this type of cuts, the granate.